Influence of different width/height ratio of maxillary anterior teeth in the attractiveness of gingival smiles - Ana Carolina Guimarães Borges; Mayra Reis Seixas; Andre Wilson Machado (Dental Press Editora, 2012)
OBJECTIVE: To evaluate, among laypersons and orthodontists, the influence of the width/height proportions of upper anterior teeth on the smile attractiveness, in photographs of close up smile from three adult Caucasian women, with 4 mm of gingival exposure. METHODS: The photographs of close up smiles were digitally manipulated and six images were created from each smile with teeth's width/height proportions in 65%, 70%, 75%, 80%, 85% and 90%. Then, all these images were manipulated again and a black mask covering all teeth from the lower arch was created. The figures were then assessed by 60 evaluators, 30 orthodontists and 30 laypersons, who assigned, in a visual analog scale, the level of attractiveness of each image. RESULTS: The obtained results, in general, showed that the proportions of 75%, 80% and 85% received the highest scores while the proportion of 65% received the lowest scores, for both groups of examiners (p < 0.05). When orthodontists and laypersons were compared, it was not found, in most situations, a significant statistical difference between their assessments (p > 0.05). Yet, the comparison between scores assigned to smiles with and without inferior teeth showed that, for all situations, there was no statistically significant difference between them (p > 0.05). CONCLUSION: For patients with gingival smile, the width/height proportions of upper anterior teeth considered more esthetic were the ones of 75%,80% and 85% for laypersons and orthodontists, and the presence or absence of inferior teeth did not affect the attractiveness level of the assessed smiles. OBJETIVO: avaliar, entre leigos e ortodontistas, a influência da alteração das proporções largura/altura dos dentes anterossuperiores na atratividade do sorriso, em fotografias do sorriso aproximado de três mulheres leucodermas adultas, com 4mm de exposição gengival. MÉTODOS: as fotografias dos sorrisos aproximados foram manipuladas em computador e seis imagens foram criadas para cada sorriso com as proporções largura/altura dos dentes em 65%, 70%, 75%, 80%, 85% e 90%. Em seguida, todas essas imagens foram novamente manipuladas e criou-se uma máscara preta cobrindo todos os dentes da arcada inferior. As imagens foram, então, julgadas por 60 avaliadores, 30 ortodontistas e 30 leigos, que aferiram, em uma escala visual analógica, o nível de atratividade de cada imagem. RESULTADOS: os resultados encontrados, em geral, demonstraram que as proporções de 75%, 80% e 85% receberam as maiores notas enquanto a de 65% recebeu as menores notas, para os dois grupos de examinadores (p<0,05). Quando os ortodontistas e leigos foram comparados, não foi encontrada, na grande maioria das situações, diferença estatística significativa entre seus julgamentos (p>0,05). Ainda, a comparação entre as notas aferidas aos sorrisos com e sem os dentes inferiores mostrou que, para todas as situações, não houve diferença estatisticamente significativa entre elas (p>0,05). CONCLUSÃO: para pacientes com sorriso gengival, as proporções largura/altura dos dentes anterossuperiores consideradas mais estéticas foram as de 75%, 80% e 85% para leigos e ortodontistas, e a presença ou não dos dentes inferiores não influenciou no nível de atratividade dos sorrisos pesquisados.